The phosphodiesterase 4 inhibitor roflumilast is effective in the treatment of allergic rhinitis - Schmidt, Bernhard; Kusma, Matthias; Feuring, Martin; Timmer, Wolfgang E.; Neuhäuser, Markus; Bethke, Thomas; Stuck, Boris; Hörmann, Karl; Wehling, Martin (The journal of allergy and clinical immunology, 2001)
Background: The beneficial effects of phosphodiesterase 4 (PDE4) inhibitors in allergic asthma have been shown in previous preclinical and clinical studies. Because allergic rhinitis and asthma share several epidemiologic and pathophysiologic factors, PDE4 inhibitors might also be effective in allergic rhinitis. Objective: The main objective of this study was to investigate the efficacy of oral roflumilast (500 μg/day) in allergic rhinitis. Methods: In a randomized, placebo-controlled, double-blinded, crossover study, 25 subjects (16 male, 9 female; median age, 28 years) with histories of allergic rhinitis but asymptomatic at screening received roflumilast (500 μg once daily) and placebo for 9 days each with a washout period of at least 14 days in between treatment periods. In each of the treatment periods, controlled intranasal allergen provocation with pollen extracts was performed daily beginning the third day of treatment, each time approximately 2 hours after study drug administration. Five and 30 minutes after each allergen provocation, rhinal airflow was measured by means of anterior rhinomanometry and the subjective symptoms obstruction, itching, and rhinorrhea were assessed by means of a standardized visual analog scale. Results: Rhinal airflow improved almost consistently during the 9 days of roflumilast treatment, and it was significantly higher at study day 9 on roflumilast in comparison with placebo, a result also found for itching and rhinorrhea. With respect to the subjective obstruction score, a significant difference in comparison with placebo could be demonstrated within 4 days. Conclusion: This study shows that a PDE4 inhibitor, roflumilast, effectively controls symptoms of allergic rhinitis. Thus PDE4 inhibitors might be a future treatment option not only in allergic asthma but also in allergic rhinitis or the combination of the 2 diseases. (J Allergy Clin Immunol 2001;108:530-6.)
Elektronische Reproduktion der Druck-Ausgabe vom 25 Mai 2002
Gesehen am 03.08.2022